Increase in ocean-onto-land droughts and their drivers under anthropogenic climate change - Guan, Y; Gu, X; Slater, L; Yin, J; Li, J; Gebrechorkos, S; Zhang, X; Kong, D; Yan, X (Springer Nature, 2023)
Ocean-onto-land droughts (OTLDs)—i.e., droughts originating over the oceans and migrating onto land—are a recently identified phenomenon with severe natural and human impacts. However, the influence of anthropogenic emissions on past and future changes in OTLDs and their underlying mechanisms remain unclear. Here, using precipitation-minus-evaporation deficits to identify global OTLDs, we find OTLDs have intensified due to anthropogenic climate change during the past 60 years. Under a future high-emissions scenario, the OTLDs would become more frequent (+39.68%), persistent (+54.25%), widespread (+448.92%), and severe (+612.78%) globally. Intensified OTLDs are associated with reduced moisture transport driven by subtropical anticyclones in the northern hemisphere and complex circulation patterns in the southern hemisphere. The reduction in moisture transport during OTLDs is mainly caused by the atmospheric thermodynamic responses to human-induced global warming. Our results underscore the importance of improving understanding of this type of drought and adopting climate mitigation measures.